„CHIŃSKI NORWID” A MYŚL I POETYKA NORWIDOLOGII POLSKIEJ. - Skalińska, Ewangelina (Colloquia Litteraria, 2014)
„Chinese Norwid” and the thought and poetics of Polish Norwid studies Review of Krzysztof Andrzej Jeżewski, Cyprian Norwid a myśl i poetyka Kraju Środka [Cyprian Norwid and the thought and poetics of the Middle Kingdom]. The review discusses main research questions tackled by Krzysztof Andrzej Jeżewski, the author of a comparative essay that juxtaposes selected aspects of Chinese culture and aesthetics with Cyprian Norwid’s works.